2010
DOI: 10.1088/1674-1056/19/10/106802
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of both composition and strain distributions in InGaN epitaxial film using x-ray diffraction techniques

Abstract: The composition and stain distributions in the InGaN epitaxial films are jointly measured by employing various x-ray diffraction (XRD) techniques, including out-of-plane XRD at special planes, in-plane grazing incidence XRD, and reciprocal space mapping (RSM). It is confirmed that the measurement of ( 204) reflection allows a rapid access to estimate the composition without considering the influence of biaxial strain. The two-dimensional RSM checks composition and degree of strain relaxation jointly, revealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[2][3][4] The unintentionally miscut, particularly those of large-diameter Si wafers, is up to 0.5 . We found that such an unintentionally miscut could lead to a tilt of $0.2 between the GaN (0002) and Si (111) atomic planes, contributed by the Nagai tilt, misfit dislocations, and/ or dislocation bendings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] The unintentionally miscut, particularly those of large-diameter Si wafers, is up to 0.5 . We found that such an unintentionally miscut could lead to a tilt of $0.2 between the GaN (0002) and Si (111) atomic planes, contributed by the Nagai tilt, misfit dislocations, and/ or dislocation bendings.…”
mentioning
confidence: 99%
“…Therefore, the research community often uses GaN epilayers as the reference. [4][5][6] In our paper, we used the phrase "currently favored method" to refer to the method used by some researchers where the GaN epilayer is chosen as the reference with the implicit assumption that it is relaxed. This is typically exemplified in papers where XRD measurements of strain and alloy composition are reported based solely on 2h-x (or x-2h) curves or based on reciprocal space maps with no absolute referencing (either to a substrate or properly selfreferenced epilayers).…”
mentioning
confidence: 99%